Study of a partially failed landslide and delineation of piping phenomena by vertical electrical sounding (VES) in the Wayanad Plateau, Kerala, India - K. S. Sajinkumar; R. Castedo; P. Sundarajan and V. R. Rani (Nat Hazards, 2015)
A partially failed landslide resembling a cascade and which imparted a step- like topography occurred on 7 July 2007 during the south-west monsoon in Erumakolli tea estate near Meppadi in Wayanad district, Kerala. Five steps (towards north) were identified in the area, with the last step being the most devastating. The landslide ruined two houses and damaged several houses. The landslide also caused widespread damage to property. Subsidence and piping also occurred in this area. Development of haphazard ground cracks is common. Vertical electrical sounding was used to identify the subsurface nature of the piping phenomena. A low-resistivity zone (\100 X m) was identified and is suspected to be the possible focus of sliding due to oversaturation in rainy seasons. This study aimed at deciphering the piping phenomena and the mechanism of failure through geophysical studies